2018
DOI: 10.1002/pbc.27516
|View full text |Cite
|
Sign up to set email alerts
|

Future health of AYA survivors

Abstract: Adolescent and young adult (AYA) oncology patients (ages 15–39) have been identified as a group with healthcare disparities including gaps and challenges in diagnosis, access to care, research, clinical trial participation, and cure rates. Like other patient groups with cancer or other chronic illnesses, disparities can lead to poor future health and outcomes, which is a well‐recognized concern within the AYA population. Cancer is the leading disease‐related cause of death in this age range. Numerous intereste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…After review of the titles and abstracts, 41 studies were identified as potentially eligible for inclusion. After full review, four systematic reviews were excluded (Levine et al, 2015;Lopategui et al, 2017;van Dorp et al, 2016;Burkart et al, 2019), one publication because data could not be extracted (Zynda et al, 2012), 15 original studies because of the absence of a healthy control group (Carter et al, 2006;Kiserud et al, 2007;Sudour et al, 2010;Speiser et al, 2011;Hamre et al, 2012;Hansen et al, 2013;Reinmuth et al, 2013;Shepherd et al, 2006;Greaves et al, 2014;Naessén et al, 2014;Hoshi et al, 2015;Wu et al, 2015;Yonemoto et al, 2016;Shandley et al, 2017;Nichols et al, 2018) and three additional studies because they generically referred to reproductive prognosis after cancer without splitting data for cancer subtypes (Green et al, 2009;Reulen et al, 2009;Dillon et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…After review of the titles and abstracts, 41 studies were identified as potentially eligible for inclusion. After full review, four systematic reviews were excluded (Levine et al, 2015;Lopategui et al, 2017;van Dorp et al, 2016;Burkart et al, 2019), one publication because data could not be extracted (Zynda et al, 2012), 15 original studies because of the absence of a healthy control group (Carter et al, 2006;Kiserud et al, 2007;Sudour et al, 2010;Speiser et al, 2011;Hamre et al, 2012;Hansen et al, 2013;Reinmuth et al, 2013;Shepherd et al, 2006;Greaves et al, 2014;Naessén et al, 2014;Hoshi et al, 2015;Wu et al, 2015;Yonemoto et al, 2016;Shandley et al, 2017;Nichols et al, 2018) and three additional studies because they generically referred to reproductive prognosis after cancer without splitting data for cancer subtypes (Green et al, 2009;Reulen et al, 2009;Dillon et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…A cancer diagnosis in one's 20s and 30s often results in a host of short and long-term adverse effects, including depression, anxiety, sleep disturbance, fatigue, pain, and loneliness. 1,2 Recent research suggests that behavioral interventions, such as mindfulness training, are feasible for young adult cancer survivors, and may reduce uncertainty, emotional distress, and improve quality of life in this population. [3][4][5] In fact, the use of mindfulness practices by young adults have steadily increased over the past two decades, suggesting that mindfulness interventions may be well accepted by this population.…”
Section: Introductionmentioning
confidence: 99%
“…First, the discussion of such services is usually framed in the context of addressing gaps in care needs or serving as examples for contextualizing the principles of survivorship follow-up care provision. [29][30][31][32][33][34] Thus, current recommendations for a systematic survivorship service construction lack granularity and specificity. Second, only a few studies have incorporated the perspectives of health care professionals (HCPs) who play a paramount role in designing and initiating such survivorship services in tertiary and community settings.…”
Section: Introductionmentioning
confidence: 99%